Upaya Meningkatkan Kinerja Karyawan melalui Kompetensi dan Pelatihan dengan Motivasi sebagai Variabel Mediasi - Abdul Chatim Pramono; Faula Arina; Wulan Ramdhani; Uchtya Nufus (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of competence and training on employee performance with motivation as a mediating variable at PT XYZ. In an era of intense competition, competence and training are considered key factors in improving employee performance. This research employs a quantitative method with a survey approach involving 376 employees of PT XYZ, selected using stratified random sampling to ensure proportional representation across divisions. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS 3.0 software to test the proposed hypotheses. The results show that competence and training have a positive and significant effect on employee performance, with motivation acting as a mediating variable that strengthens the relationship. These findings provide important implications for management, particularly in designing effective training and competency development programs to enhance employee performance. Nevertheless, this study is limited by the sample scope and the generalizability of its findings, suggesting the need for future research with broader coverage.